Pengaruh Kompetensi Manajerial Kepala Sekolah terhadap Peningkatan Kinerja Guru MIS. Mathla'ul Anwar se-Desa Leuwibatu - Ihsan, Muzhir; Anisa, Mila Nur (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The performance of teachers plays a crucial role in achieving educational goals, and it is strongly influenced by the leadership and managerial competence of school principals. This research was conducted to examine the influence of principals' managerial competence on the performance of teachers at MIS Mathla’ul Anwar in Leuwibatu Village. Managerial competence includes aspects such as planning, organizing, evaluating, and leading, which are essential for creating a supportive and effective school environment. This study employed a quantitative approach using a survey method. The population consisted of all 24 classroom teachers at MIS Mathla’ul Anwar, and a saturated sampling technique was used. Data were analyzed using simple linear regression with SPSS version 25, preceded by descriptive analysis, data quality tests, classical assumption tests, and hypothesis testing. The results showed that the principal's managerial competence has a significant and positive influence on teacher performance, particularly in areas of lesson preparation, delivery, and assessment. This suggests that the more competent the principal is in managing the school, the better the teachers perform. However, the study also indicates that other factors such as teacher professionalism, availability of learning facilities, and support from the school environment also contribute to teacher performance.